Identification of Medicinal Plants and Their Utilization by Community in Kendal Village, Kendal Sub-district - Hanum, Aghnia Rahmi; Wijayanti, Erna (Biology, Medicine, & Natural Product Chemistry, 2023)
Traditional medicine is a cultural heritage from ancestors deeply rooted in the nation's heritage; therefore, its use is still based on spoken and written experience from generation to generation. Even though most people have turned to modern medicine, some still use these medicinal plants as ingredients for medicine, food, and other processed consumption. This study aims to identify the types of medicinal plants found in Kendal village and how to use them, obtain them, and then transform them into effective medications. This study employs qualitative descriptive methodologies. Observation and interviews are employed to collect data. Based on the results of community interviews, it was determined that many Kendal village residents continue to use plants to treat various diseases. The plant parts utilized are rhizomes, leaves, and stems. This medicinal plant has various uses, ranging from direct consumption to boiling.